Formulation of Business Development Strategy Through SWOT Approach and Business Model Canvas (Case Study on MSMEs in Padamulya Village) - Lestari, Fitri; Muttaqin, Ridlwan (International Journal of Finance Research, 2024)
This study highlights the important role of micro, small, and medium enterprises (MSMEs) in the local and national economy, especially in developing countries. It focuses on Padamulya Village in Pasirwangi District, Garut Regency. MSMEs in this village are the driving force of the regional economy through their ability to create jobs and adapt to technological changes. This study uses a qualitative approach to analyze MSME development strategies in Padamulya through SWOT analysis and Business Model Canvas (BMC). The purpose of the study is to identify the challenges faced by MSMEs, including limited capital, technology, and market access, and to formulate effective development strategies in the era of globalization. The study results indicate that MSMEs in Padamulya are in a growth phase focusing on increasing short- and medium-term profitability and product and technology innovation. Through product diversification, quality improvement, and the development of distribution channels, MSMEs in this village can strengthen their competitiveness in domestic and international markets. This study guides policymakers and MSME actors in optimizing local potential and strengthening the regional economy. It also underscores the need for further studies on implementing BMC in other MSMEs, highlighting the importance of continuous learning and improvement in the field of business development.